2008
DOI: 10.1007/s11947-008-0106-6
|View full text |Cite
|
Sign up to set email alerts
|

Color of Salmon Fillets By Computer Vision and Sensory Panel

Abstract: A computer vision method was developed and used to assign color score in salmon fillet according to SalmonFan™ card. The methodology was based on the transformation of RGB to L*a*b* color space. In the algorithm, RGB values assigned directly to each pixel by the camera in the salmon fillet image, were transformed to L*a*b* values, and then matched with other L*a*b* values that represent a SalmonFan score (between 20 and 34). Colors were measured by a computer vision system (CVS) and a sensorial panel (eight pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
1
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(77 citation statements)
references
References 30 publications
3
69
1
4
Order By: Relevance
“…On the contrary, when the lighting is not standard, an empirical conversion must be performed, as it is stated in previous works regarding the measurement of the colour of the solid foods. [21][22][23][24][25][26] These empirical models must be fitted by a calibration procedure using samples with known colour values. In this work, the following empirical conversion model was used, with linear and quadratic relations, as well as interactions between the RGB values:…”
Section: Image Acquisition and Processingmentioning
confidence: 99%
“…On the contrary, when the lighting is not standard, an empirical conversion must be performed, as it is stated in previous works regarding the measurement of the colour of the solid foods. [21][22][23][24][25][26] These empirical models must be fitted by a calibration procedure using samples with known colour values. In this work, the following empirical conversion model was used, with linear and quadratic relations, as well as interactions between the RGB values:…”
Section: Image Acquisition and Processingmentioning
confidence: 99%
“…Based on techniques from other studies investigating the relationship between changes in color of food products and their consumer evaluations (Abbott et al, 2004;Zhou et al, 2004;Pérez-Gago et al, 2006;Pristijono et al, 2006;Quevedo et al, 2008), the shelf-life of each apple slice was determined as the time required for browning to develop to an unacceptable level. Browning of the cut surfaces was evaluated by three referees according to a visual color scale of 1 -5, where 1 = fresh without any browning, 2 = slight browning of the cut surface, 3 = modérate browning, 4 = severe brown discoloration, 5 = complete discoloration.…”
Section: Sensory Evaluationmentioning
confidence: 99%
“…Recently, León et al (2006) demonstrated a computer visión system (CVS) for measuring color in L*a*b* coordinates from RGB space. Some studies have been undertaken to apply that approximation to food (Pedreschi et al, 2007;Quevedo et al, 2008). During the description of browning kinetics using color information, an L* mean valué is generally assumed.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the roes were drained in sieve and then separated by color according to the hexadecimal code and RGB model for color (Quevedo, Aguilera, & Pedreschi, 2010). Generally the gonads of sea urchin are divided into three color categories: yellow or bright orange, represents intact and firm texture or otherwise less intense yellow, indicates intact and firm texture also, and brown color, may be ruptured and features smooth and creamy texture (Stamatis & Vafidis, 2009).…”
Section: Methodsmentioning
confidence: 99%